(untitled) (Revista Educação, Artes e Inclusão, 2020)
This article addresses accessibility and the issues faced by wheelchair users in tourist spots. Our aim was to investigate the architectural accessibility for wheelchair users on public roads and sidewalks, in the downtown area of Caldas Novas, Goiás, Brazil. For that, a descriptive research was carried out, with a qualitative approach, divided into two phases: bibliographic and field researches. The field research was held with a group of basketball players on wheels, which moves around the city using their wheelchair on a daily basis. A quasi-standardized interview was used as a resource for data collection, with 10 open-ended questions, applied to three of these wheelchair users athletes. We conclude that the city, even being a tourist center, offers many obstacles to its population that depends on a wheelchair to move around and, therefore, to the tourists in the same conditions. Among these obstacles we can mention the free access to food courts, bathrooms, bank agencies, concerts and public events. Apart from that, people with disabilities are not united as they should, which makes it difficult to achieve new rights in society.